(untitled) (Journal of Informatics Education and Research, 2025)
Individuals in an organization have vast potential for development and it can be further developed and multiplied through appropriate and systematic efforts. An organization’s success is determined by the skills and motivation of its human capital. Competent employees are the greatest assets of any organization. By providing the right type of climate, individuals in an organization can be helped to give full contribution to achieve the goals of the organization. Therefore, to initiate HRD practices, a firm philosophy with humane and value-based approach has to be established. This will result in the establishment of HRD culture in the organization. Organizational culture includes ethics, values, beliefs, attitudes, norms, ethos, climate, environment, and culture. It can be characterized as consisting of Openness (O), Collaboration (C), Trust (T), Authenticity (A), Pro-activity (P), Autonomy (A), Confrontation (C), and Experimentation (E) and it is abbreviated as OCTAPACE. The present paper is a humble attempt to identify the major factors based on descriptive research design undertaken with the help of structured questionnaires to study OCTAPACE in FMCG Industry. The study is based on responses from 50 middle management executives from a sample of leading five FMCG companies of Indore city. This paper employs certain statistical tools for assessing whether the hypotheses that had been formed are valid or not. The results show that the sample organizations differ significantly in their OCTAPACE Culture and are having varying levels of OCTAPACE culture. The role of management executives in any human resource development exercise is crucial and centers on creation of the right environment for OCTAPACE culture, wherein people are free and attain new levels of performance for them and thereby for the organization as a whole.